Antithrombotic Stewardship: Assessing Use of Computerized Clinical Decision Support Tools to Enhance Safe Prescribing of Direct Oral Anticoagulants in Hospitalized Patients. Issue 8 (December 2021) - Ahuja, Tania; Raco, Veronica; Papadopoulos, John; Green, David
Abstract : Abstract: Prescribing patterns for oral anticoagulants in patients with nonvalvular atrial fibrillation and venous thromboembolism is shifting from vitamin K antagonists, such as warfarin to the direct oral anticoagulants (DOACs), such as dabigatran, rivaroxaban, and apixaban. Although many hospital systems have implemented clinical decision support or enhanced monitoring for patients prescribed warfarin, there is limited evidence to suggest similar levels of enhanced monitoring for DOACs. The antithrombotic stewardship team at our institution developed guidelines and implemented computerized clinical decision support (CCDS) tools to enhance medication and patient safety related to the DOACs. We sought to assess the safety and effectiveness of these CCDS tools available to clinicians upon DOAC prescription in hospitalized patients. We performed a retrospective review of 121 patients who received at least two doses of a DOAC from January 2013 to July 2014. We assessed dosing of the DOAC according to the CCDS provided upon order entry. Adherence to CCDS was 80% (n = 24), 75% (n = 46), and 87% (n = 27) in the dabigatran, apixaban, and rivaroxaban group, respectively. Our data demonstrate that implementing CCDS for DOACs into the electronic medical record may ensure safe prescribing of high-risk medications.